Nonlinear Discrete-Continuous Models in Dynamic Investigations of Plane Truss Members - Pielorz, A. (Engineering Transactions, 1997)
The paper presents dynamic investigations of plane trusses subject to longitudinal deformations, using nonlinear discrete-continuous models. An external excitation is applied to a rigid body located in a truss joint. In this joint, a discrete element with a spring having a nonlinear stiffness is also located. In the considerations the wave method is applied which enables to determine displacements, strains and velocities in arbitrary cross-sections of the truss members at an arbitrary time instant. Numerical calculations are performed for two nonlinear models of the plane truss in steady as well as in transient states.